Using Video Subscribe to Improve Students’ Speaking Ability - Refika Andriani; Adhella Putri; Destina Kasriyati (ELT-Lectura, 2021)
Based on the preliminary research, it was found that Junior High School Students of IT Al-Birru Pekanbaru’s speaking skill regarding to recount text was very poor. So, the researcher decided to conduct a Classroom Action Research by using Video Subscribe to improve their speaking skill. It can be stated that the research aims at improving the students of Junior High School of IT Al-Birru Pekanbaru’s speaking skill by using Video Subscribe. The respondents of the research were twenty students of grade VIII.1, Junior High School of IT Al-Birru Pekanbaru. This research was done in a cycle with four meetings and a test. For collecting the data, a test, an observation checklist, field notes, and an interview were distributed. After analyzing the data in cycle I, it was found that the students' speaking ability was improved. It was proved by the students’ speaking criteria score; accent was about 60; grammar was about 74; vocabulary was about 79; fluency was about 72; and comprehension was about 78. So, the average score of students’ speaking ability was 72.4. This students’ speaking improvement was influenced by a factor namely interest. In the other hands, this video subscribe was very interesting media so it could foster the students’ participation and confidence during the process of learning activity especially in speaking regarding to recount text. No more students were inactive. They tended to be focus and active in doing communication such as addressing questions and giving comments.